Theory and applications of numerical analysis - Phillips, G. M. (George McArtney); Taylor, Peter John (Academic Press, 1996)
Theory and Applications of Numerical Analysis is a self-contained Second Edition, providing an introductory account of the main topics in numerical analysis.The book emphasizes both the theorems which show the underlying rigorous mathematics andthe algorithms which define precisely how to program the numerical methods.